Legal education during COVID’19 pandemics: preliminary data from a survey to Bar interns in Lisbon. - Santos, S. (Legal Professions WG, 2021)
COVID’19 pandemics have had a serious impact in legal education, as in all other types and levels of education. In this paper, we try to measure its impacts on the Bar internship program - a previous and obligatory step in Portugal for those who have a Law degree and wish to have a professional certificate to act as lawyer (barrister or solicitor). The class of 2020 – around 700 interns - is the first to have all classes online changing the paradigm of session training based in small groups working in class with an instructor, to virtual classes using e-learning platforms. A questionnaire survey was created and made available through the e-learning platform during the months of April and May 2021. In this presentation we will be using preliminary data and will focus on the attitudes of interns towards the Bar, the quality of virtual sessions and other challenges posed by online education.